2014
DOI: 10.1002/adsc.201301129
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diverse Azolo[c]quinazolines by Palladium(II)‐ Catalyzed Aerobic Oxidative Insertion of Isocyanides

Abstract: Abstract:We report the palladium(II)-catalyzed aerobic oxidative coupling of isocyanides with various (2-aminophenyl)azoles using air as the stoichiometric oxidant. A diverse range of medicinally valuable azolo[c]quinazolines was obtained by this new approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In as imilar process,2 -(2aminophenyl)tetrazoles 129 and N-(benzimidazol-2-yl)guanidine 132 [62] proved to be suitable substrates (Scheme 32 b, c). Compared to the Pd-catalyzed process, [63] cobalt catalysis has ah igher tolerance for aliphatic and aromatic isocyanides. Unfortunately,O 2 seems not to be asuitable oxidant.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In as imilar process,2 -(2aminophenyl)tetrazoles 129 and N-(benzimidazol-2-yl)guanidine 132 [62] proved to be suitable substrates (Scheme 32 b, c). Compared to the Pd-catalyzed process, [63] cobalt catalysis has ah igher tolerance for aliphatic and aromatic isocyanides. Unfortunately,O 2 seems not to be asuitable oxidant.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In a similar process, 2‐(2‐aminophenyl)tetrazoles 129 and N ‐(benzimidazol‐2‐yl)guanidine 132 proved to be suitable substrates (Scheme b, c). Compared to the Pd‐catalyzed process, cobalt catalysis has a higher tolerance for aliphatic and aromatic isocyanides. Unfortunately, O 2 seems not to be a suitable oxidant.…”
Section: Insertions Of Isocyanides Into Heteroatom–metal Bondsmentioning
confidence: 99%
“…In the cited paper the role of catalyst and mechanism of the reaction was discussed in detail. 17 Li 18 discussed tandem synthesis of 2-(4,5-dihydrothiazol-2-yl)aniline (42) and 2-(4,5-dihydrooxazol-2-yl)aniline (41). It was shown that 2-aminobenzonitrile (34) with 2-mercaptoethylammonia chloride or 2-aminoethanol with various copper catalysts and bases formed compounds 42 and 41, respectively (Scheme 14).…”
Section: Methodsmentioning
confidence: 98%
“…41 It was shown that compounds 62 in reaction with isocyanides in different solvents formed a mixture of two isomeric heterocycles, namely, 2-substituted 5-amino [1,2,4] The structure of key compounds was proven by X-ray diffraction analysis. 41 An effective copper-catalyzed synthesis of N-substituted heterocycles using ligands for the formation of the C-N bond was discussed in the work of Subramanian and Kaliappan 42 (Scheme 38).…”
Section: The Reactivity 2-(azolyl)anilines In Cyclocondensationsmentioning
confidence: 99%
See 1 more Smart Citation